Era móvil: espacios-tiempos en contextos escolares. Los mundos de vida de las infancias - Carmona Botero, Sara (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
The increasing, generalized use of technologies in contemporary society shows the narrow bond established between such developments and the different social strata. The information and communication technologies not only constitute tools for the applied use, or the practice of a given task, but have also become constitutive part of contemporary society. Thus, technologies should be understood as extensions that have not only a physical aspect, but are also extensions of thought and human interaction, so that they have been articulated to the social, economic, political, scientific, cultural and educational dynamics of society. The ways of thinking, building and inhabiting the world have been permeated by digital devices and surroundings and, in this sense, it is necessary to reflect upon the uses and the relations established with society, thanks to the ever-accelerating proliferation of artifacts and developments of information systems.